Designing online network intrusion detection using deep auto-encoder Q-learning. (October 2019) - Kim, Chayoung; Park, JiSu
Abstract: Because of the increasing application of reinforcement learning (RL), particularly deep Q-learning algorithm, research organizations utilize it with increasing frequency. The prediction of cyber vulnerability and development of efficient real-time online network intrusion detection (NID) systems are progressions toward becoming RL-powered. An open issues in NID is the model design and prediction of real-time online data composed of a series of time-related feature patterns. There have been concerns regarding the operation of the developed systems because cyber-attack scenarios vary continuously to circumvent NID. These issues have been related to the human interaction significance and the decrease in accuracy verification. Therefore, we employ an RL that permits a deep auto-encoder in the Q-network (DAEQ-N). The proposed DAEQ-N attempts to achieve the maximum prediction accuracy in online learning systems into which continuous behavior patterns are fed and which are trained with more significant weights by classifying it as either "normal" or "anomalous."